PERTIMBANGAN HAKIM DALAM PUTUSAN BEBAS DAN REHABILITASI HAK TERDAKWA:ANALISIS PUTUSAN NO 3/PID.PRA/2025/PN Amb DALAM PERSPEKTIF HUKUM PIDANA ISLAM - Sumantri Ritonga; Imam Yazid (Public Sphere: Jurnal Sosial Politik, Pemerintahan dan Hukum, 2026)
Acquittal verdicts in criminal cases are not always followed by the optimal restoration of the defendant's rights, particularly in cases of error in persona (mistaken identity), which consequently continues to give rise to issues concerning justice and the accountability of law enforcement officials. The problem arises when the mechanisms of rehabilitation and compensation provided to the defendant have not been fully capable of restoring the losses incurred as a result of the actions of law enforcement officials. This research aims to analyze the judges' considerations in Decision Number 3/Pid.Pra/2025/PN Amb, the implementation of the restoration of the defendant's rights following the acquittal, and its relevance from the perspective of Islamic criminal law. This research constitutes a normative legal study employing a statutory approach, a case approach, and a conceptual approach, analyzed qualitatively using descriptive analytical techniques. The data sources comprise court decisions, legislation, and literature on both national criminal law and Islamic criminal law, all analyzed qualitatively. The findings indicate that the judges' considerations in imposing the acquittal were based on the failure to fulfill the elements of proof as required under criminal procedural law. Although the judge granted rehabilitation and material compensation to the defendant, the restoration of immaterial losses and the accountability of law enforcement officials have not yet fully delivered a sense of justice. From the perspective of Islamic criminal law, the act of wrongful arrest which causes harm to an individual contradicts the principles of justice, the protection of human honor (hifzh al-'irdh), and the principle of liability (dhaman). This research contributes by offering an analysis that integrates the perspectives of positive law and Islamic criminal law in assessing the effectiveness of the restoration of the rights of victims of procedural error. Therefore, the restoration of the rights of victims of procedural error should not be limited to the rehabilitation of reputation alone, but must also involve accountability mechanisms against the party responsible for the loss.AbstrakPutusan bebas dalam perkara pidana tidak selalu diikuti dengan pemulihan hak terdakwa secara optimal, terutama dalam kasus kesalahan proses hukum (error in persona), sehingga masih menimbulkan persoalan keadilan dan pertanggung jawaban aparat penegak hukum. Permasalahan muncul ketika mekanisme rehabilitasi dan ganti kerugian yang diberikan kepada terdakwa belum sepenuhnya mampu memulihkan kerugian yang timbul akibat tindakan aparat penegak hukum. Penelitian ini bertujuan menganalisis pertimbangan hakim dalam Putusan Nomor 3/Pid.Pra/2025/PN Amb, pelaksanaan pemulihan hak terdakwa setelah putusan bebas, serta relevansinya menurut perspektif hukum pidana Islam. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan, pendekatan kasus, dan pendekatan konseptual yang dianalisis secara kualitatif menggunakan teknik analisis deskriptif. Sumber data penelitian berupa putusan pengadilan, peraturan perundang-undangan, serta literatur hukum pidana nasional dan hukum pidana Islam yang dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa pertimbangan hakim dalam menjatuhkan putusan bebas didasarkan pada tidak terpenuhinya unsur pembuktian sebagaimana dipersyaratkan dalam hukum acara pidana. Meskipun hakim telah memberikan rehabilitasi dan ganti kerugian materiil kepada terdakwa, pemulihan terhadap kerugian immateriil dan pertanggungjawaban aparat penegak hukum belum sepenuhnya memberikan rasa keadilan. Dalam perspektif hukum pidana Islam, tindakan salah tangkap yang merugikan individu bertentangan dengan prinsip keadilan, perlindungan kehormatan manusia (hifzh al-'irdh), serta prinsip tanggung jawab (dhaman). Penelitian ini memberikan kontribusi dengan menawarkan analisis yang mengintegrasikan perspektif hukum positif dan hukum pidana Islam dalam menilai efektivitas pemulihan hak korban kesalahan proses hukum. Oleh karena itu, pemulihan hak korban kesalahan proses hukum tidak hanya berupa rehabilitasi nama baik, tetapi juga membutuhkan mekanisme pertanggungjawaban terhadap pihak yang menyebabkan kerugian.